Multicomponent induced localized coupling in Penrose tiling for electromagnetic wave absorption and multiband compatibility. (10th December 2022) - Ma, Xinran; Duan, Yuping; Huang, Lingxi; Ma, Ben; Lei, Hao
Highlights: Design quasiperiodic absorbers with long-range order but no periodicity. Explored the relationship between electromagnetic parameters and frequency by structural design and component selection in depth. The effective absorption bandwidth of Penrose absorber can realize 9.32 GHz in 2 mm thickness. The multilayer metamaterials perfectly unify radar-infrared compatible capability. Abstract: In the electronic information and intelligent era, microwave absorption materials have been focused on the issue of electromagnetic (EM) pollution, but high-performance absorbers with thin thickness are highly desirable. The positive action between structural design and component selection can be regarded as a function to optimize the microwave loss capacity, which contributes to understanding the response mechanisms from the micro and macro. Therefore, we designed the absorber with quasiperiodic structures of Penrose tiling that has finely engineered the location of maximum absorption peak, the spherical carbonyl iron in thin rhombus, and flakey carbonyl iron in fat rhombus, the effective absorption bandwidth (Reflection Loss ≤ –10 dB) was realized from 6.46 GHz to 15.78 GHz in the 2 mm thickness. The unique arrangement of Penrose tiling can respond alternatingly to EM waves at large scales, and multicomponent coupling is distinctly in the neighboring unit cells. In addition, spraying aluminum pigment as the upper layer, the infrared emissivity is less than 0.35 to meet the complex application environment. This work opens up novel ideas on quasiperiodic structure combined multicomponent and injects infinite vitality to provide prospects for broadband responsive and high-efficiency EM absorbers.